Evaluation of Material Technical Engineering Department Performance by Staff Member and student in Technical College -Baghdad - ابراهيم, صنعاء مولود (Journal of Economics and Administrative Sciences, 2013)
The research intent evaluates the performance of material technical department / Technical College -Baghdad.The study depend on the descriptive analytical approach to determine and treating the variables to get data and information that related to study, the researchers depended on questionnaire designed for this purpose and contains eight main dimensions that’s are scientific reference , academy course, staff member , administrative system, physical facilities , student ,scientific research, graduate service , in addition each dimension  involved (5) items contacted with mean dimensions, which translate aspects of  performance evaluation, the questionnaire applied on two samples staff members & student in searched department which are (13) staff members, represent (%72) from total staff members and (24) students represent(%29) from total student in searched society , in addition the research dependent on different measurements that are developed to coincides with the study objectives and the nature of the investigated environment . To treating data, many statically tools have been used the frequencies, the means, the percentage the standard deviations and covariance for searched number. The study resulted it is necessary to depended performance evaluate concept on current century in  education sector to reach to excellent levels in performance and actualize perpetual advantages searched department, in end the study ending with group of suggestion and recommendations like its necessity support  student science levels throw ensure the main reference  by a good  quality and low price and also ensure educational tools and also support students to get jobs after ending the study by coordinate with companies as a competitive advantage to researched department .